GENESIS OF SCIENTIFIC IDEAS ABOUT THE ROLE OF THE STATE IN MANAGING SOCIO-ECONOMIC DEVELOPMENT - Stativka N. V.,; Bubliy M. P., (Pressing Problems of Public Administration, 2021)
The article examines the theoretical foundations of interaction between government bodies and the public in the communication space. It is proved that over the years of independence of our country, relations between the government and society have been transformed, from a paternalistic model to a real, mutually beneficial, Democratic in nature, bilateral interaction.Relations between government and society have been transformed in such a way that there is an opportunity (and the need at the same time) for real interaction between state authorities and management with civil society structures that are able to solve together current and most important socio-economic and social problems by combining resources.Thus, we believe that positive practices of electronic interaction between authorities and society should be institutionalized while defining criteria that will determine the effectiveness of the existing mechanisms of direct democracy and the degree of their compliance with public needs.It is determined that the achieved level of informatization allows us to fully develop the Institute of e-democracy, as the latest tool for improving the quality of managerial decision-making at the state level with the help of a multi-level expert online network consisting of all categories of citizens.Having analyzed a large factual material, the regulatory legal framework related to the informatization of state authorities and society, we can draw the main conclusion that in Ukraine the vector for institutionalization of the processes of formation of political and administrative electronic interaction between government and society and the formation of “electronic democracy” has already been indicated.